PENERAPAN MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA INTERAKTIF PADA MATERI SISTEM PENCERNAAN MANUSIA DALAM MATA PELAJARAN IPA KELAS V SDN 98 BONTOMANAI BULUKUMBA - A. Nur Akbar; Nurlina, Nurlina; Magfirah, Nurul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Application of Interactive Multimedia-Based Learning Media in Human Digestive System Material in Science Subjects for Class V Students at SDN 98 Bontomanai, Bulukumba Regency. This type of research is pre-experimental research, the aim of the research is to determine students' knowledge before implementing interactive multimedia-based learning media, to determine students' knowledge after implementing interactive multimedia-based learning media and to determine the increase in students' knowledge before and after implementing interactive multimedia-based learning media. in the science subject material on the human digestive system for class V at SDN 98 Bontomanai Bulukumba. The research results showed that the average score at the pretest was 34.74, categorized as low and incomplete, whereas after applying interactive media, at the posttest, the average score was categorized as high and completed, namely 82.64. In the results of the N-gain test, the average value of students is categorized as high, namely 0.75 with N-gain > 0.7. Based on the research results above, it can be concluded that the application of interactive media can increase students' knowledge in science subjects regarding the human digestive system. class V at SDN 98 Bontomanai Bulukumba.